INISIASI INOVASI PENGOLAHAN IKAN ASAP TRADISIONAL MELALUI TEKNOLOGI ASAP CAIR DAN METODE SANITASI-PENGEMASAN: STUDI KASUS KUB BERKAH ABADI, TRENGGALEK - Pramono, Heru; Andriyono, Sapto; Pangestu, Chandra Trisna; Ulum, Miftakhul; Haris, Mochamad (Universitas Mataram, 2025)
The smoked fish industry produces more than 175,522 tons of fish per year, but the technology used is generally simple and relies on hot smoking techniques. The Berkah Abadi Joint Business Group (KUB) is located in Munjungan, Trenggalek Regency, an area bordering the sea and mountains. Initial studies indicate that KUB Berkah Abadi's smoked fish processors face obstacles related to production methods, product sanitation and hygiene, and marketing. The goal of this community service program is to transfer processing technology, improve sanitation and hygiene, and implement vacuum packaging technology to enhance marketing efforts. Twenty participants successfully completed the community service activity. The program began with a survey on liquid smoke and its applications. Then, participants received counseling and practiced smoking fish with liquid smoke technology. Finally, they implemented what they learned by packing smoked fish with a vacuum sealer. The results of the program showed that 90% of the participants increased their knowledge of liquid smoke technology and mastered the vacuum sealer packaging method. They also understood the importance of sanitation and hygiene implementation. Further community service is needed to determine the development of product marketing results after technology implementation.